INVESTIGATING ESP STUDENTS' DIGITAL LITERACY PRACTICES: A CASE OF COMMUNICATION SCIENCE STUDENTS - Canda Putri Anggini, - (2022)
The emergence of technology has changed the way people practice literacy into digital one. This condition has made people, including students in higher level, use more digital tools and internet as the assistance to make and share meaning. This study was intended to find ESP students' digital literacy practices and the affecting factors. The framework employed in this study was proposed by Hague and Payton (2010) which defined it as an ability to create and share meaning through different formats. Their concept consisted of eight components of digital literacy, namely functional skills, e-safety, effective communication, ability to find and select information, collaboration, cultural and social understanding, critical thinking and evaluation, and creativity. The subjects included were 184 Communication Science students enrolling ESP class. This study employed case study design with interview, observation, and questionnaire as the instruments of data collection. The result of the study indicated that ESP students did various tasks which demanded creativity and collaboration in various formats. They also collaborated by using digital tools such as discussing and sharing their tasks in digital platforms. In addition, they differentiate the way they communicate according to the age and purpose of the communication. They were also able to find, evaluate and select information they acquired by comparing and contrasting several sources. The students respected other cultures during the interaction with other people by not saying bad words or comments to others. They also consider the safety in finding information by keeping the password as a secret and avoid cyber bullying by not giving bad comment and respect others' privacy. Their digital literacy practices were mostly affected by the lack of supporting facilities, supported resources, supported learning materials, students' skills, and time to practices the digital literacy in the classroom. It is suggested that ESP teachers implement the eight components of digital literacy and It is also highly recommended that the higher education institution provides resources and facilities to support ESP learning and facilitates training to improve the digital skills of students and teachers.